2005
DOI: 10.1063/1.1850402
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic structure of the local-moment antiferromagnet CeCuSn

Abstract: Articles you may be interested inCrystal structure and magnetic properties of R5Sn4 alloys, where R is Tb, Dy, Ho, and Er J. Appl. Phys. 109, 07A917 (2011); 10.1063/1.3549562 Effect of temperature on hybridization and magnetism in UPdSn and UCuSn

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
(11 reference statements)
2
7
0
Order By: Relevance
“…1 would only contribute to reciprocal lattice wave vectors. Magnetic ordering observed in this compound gives satellites at (h±τ ,0,0) with τ = 0.115 as reported near each reciprocal lattice wave vectors 40 . This value appears as the average of Ch(1), Ch(2) and Ch(4) in Table II but the zone center is at 1/2 in reciprocal space and not near a structural reciprocal lattice wave vector.…”
Section: 11515supporting
confidence: 68%
“…1 would only contribute to reciprocal lattice wave vectors. Magnetic ordering observed in this compound gives satellites at (h±τ ,0,0) with τ = 0.115 as reported near each reciprocal lattice wave vectors 40 . This value appears as the average of Ch(1), Ch(2) and Ch(4) in Table II but the zone center is at 1/2 in reciprocal space and not near a structural reciprocal lattice wave vector.…”
Section: 11515supporting
confidence: 68%
“…CeCuSn has most intensively been investigated [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. But the structure of CeCuSn has so far only been investigated on the basis of powder diffraction data, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic, resistivity and specific heat studies on single-crystal and polycrystalline CeCuSn exhibits complex magnetic ordering in this compound [11][12]20]. Sakurai et al observed antiferromagnetic ordering (T N ) around 8 K in arc-melted CeCuSn, which also exhibited weak spontaneous magnetization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations